2022
DOI: 10.1038/s41467-021-26615-y
|View full text |Cite
|
Sign up to set email alerts
|

The DNA methylome of cervical cells can predict the presence of ovarian cancer

Abstract: The vast majority of epithelial ovarian cancer arises from tissues that are embryologically derived from the Müllerian Duct. Here, we demonstrate that a DNA methylation signature in easy-to-access Müllerian Duct-derived cervical cells from women with and without ovarian cancer (i.e. referred to as the Women’s risk IDentification for Ovarian Cancer index or WID-OC-index) is capable of identifying women with an ovarian cancer in the absence of tumour DNA with an AUC of 0.76 and women with an endometrial cancer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…We have demonstrated the unprecedented performance of a comprehensive DNA methylation classifier — the WID-CIN test — in identifying hrHPV-pos women with or at future risk of CIN3+. The fact that the test principle (i.e., analysis of DNAme of a combination of CpGs on an array) not only identifies women with CIN3+ but also women with ovarian [ 37 ] and breast cancer [ 29 ] (WID-OC and WID-BC) suggests that the WID-CIN test could be rapidly prioritized for cost-effectiveness analyses and potential quick implementation in the clinical arena. In addition to array-based detection of CIN3+, in ongoing work, we have developed a multiplexed MethyLight PCR-based test, the WID-qCIN test, that amplifies regions in the genes DPP6 , RALYL , and GSX1 and exhibits excellent sensitivity and specificity in both diagnostic and predictive settings (Herzog, Sundström et al, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated the unprecedented performance of a comprehensive DNA methylation classifier — the WID-CIN test — in identifying hrHPV-pos women with or at future risk of CIN3+. The fact that the test principle (i.e., analysis of DNAme of a combination of CpGs on an array) not only identifies women with CIN3+ but also women with ovarian [ 37 ] and breast cancer [ 29 ] (WID-OC and WID-BC) suggests that the WID-CIN test could be rapidly prioritized for cost-effectiveness analyses and potential quick implementation in the clinical arena. In addition to array-based detection of CIN3+, in ongoing work, we have developed a multiplexed MethyLight PCR-based test, the WID-qCIN test, that amplifies regions in the genes DPP6 , RALYL , and GSX1 and exhibits excellent sensitivity and specificity in both diagnostic and predictive settings (Herzog, Sundström et al, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…We were the first to demonstrate that epigenetic analyses on self‐samples are highly promising for cervical 68 and endometrial 69 cancer detection and have described epigenetic field defects preceding breast, 70 ovarian 71 and cervical 72,73 cancer. Very recently, we demonstrated that DNAme signatures derived in cervical smear samples are capable of detecting/predicting women with ovarian cancer, that is, the WID‐OC test 74 and poor prognostic breast cancer, that is, the WID‐BC test 75 . The WID‐OC test was developed to identify/predict women with ovarian cancer, the majority of which arises from Müllerian Duct structures 76 .…”
Section: Utilizing Dna Methylation In Cervical Samples the Future Of ...mentioning
confidence: 99%
“…The WID‐OC test was developed to identify/predict women with ovarian cancer, the majority of which arises from Müllerian Duct structures 76 . In line with the idea of an epigenetic field defect is the observation that the WID‐OC test, which does not rely on the presence of tumor DNA in the sample, is able to identify endometrial cancer cases with a Receiver Operating Characteristic Area Under the Curve of 0.81 in samples with no detectable endometrial cancer DNA 74 . Finally, our yet unpublished data demonstrate that DNAme signatures can both detect and predict the future risk of cervical and endometrial cancer.…”
Section: Utilizing Dna Methylation In Cervical Samples the Future Of ...mentioning
confidence: 99%
“…Moreover, Barrett et al recently demonstrated that the DNA methylome in cervical samples can predict the risk of ovarian cancer with about 75% certainty. 18 Evaluation of the vaginal microbiome as a possible early detection method could also be promising. The microbiome might impact estrogen metabolism and may influence the risk of ovarian cancer, like exogenous estrogens.…”
Section: Discussionmentioning
confidence: 99%